PELATIHAN SENAM AYO BERGERAK, SENAM BUGAR INDONESIA LEBIH MENINGKATKAN KEBUGARAN FISIK DARIPADA SENAM AYO BERSATU PADA WANITA ANGGOTA KLUB SENAM LALA STUDIO DENPASAR - Bawiling, Nancy Sylvia; Adiputra, Nyoman; Tirtayasa, Ketut (Sport and Fitness Journal; Volume 2, No.1, 2014)
The patterns of women’s daily working, shift from dynamic to static state due to the influence of technology that makes the daily work more effectively and efficiently, which constantly lowering physical fitness. Aerobic exercise is a physical activity that can increase women’s physical fitness, these include Ayo Bergerak , Bugar Indonesia and Ayo Bersatu Gymnastic Exercise.This study was aimed to determine which gymnasticic exercise is more effective to improving physical fitness. This study is a randomized experimental design with Pre and Post Test Control Group Design on 30 women aged 30-40 years with a poor of physical fitness, divided into 3 groups randomly which Group I was given training of Ayo Bergerak Gymnastic Exercise, Group II with Bugar Indonesia Gymnastic Exercise and group III with Ayo Bersatu Gymnastic Exercise, 3 times perweeks during 10 weeks. The value of physical fitness was measured using the Kasch Step Test method, calculated the recovery heart rate (RHR) after step test, with assuming that the recovery heart rate decreased after training, which indicates increased physical fitness. The Shapiro - Wilk test and Levene test obtained p > 0.05, indicating the overall sample homogeneity qualify. Paired sample t-test and statistical ANOVA-test obtained p < 0.05 indicates that the three exercise are effectively improved physical fitness. And effectiveness test after training by using independent t- test showed Ayo Bergerak and Bugar Indonesia Gymnastic Exercise are the most highly improved physical fitness. For women who want to improve their physical fitness can choose both of the exercise.
Keywords: physical fitness, physical exercise, ayo bergerak gymnastic exercise, bugar indonesia gymnastic exercise, ayo bersatu gymnastic exercise